Effect of Polydeoxyribonucleotide Injection in a Patient With Carpal Tunnel Syndrome. (October 2018) - Park, Jin-Sung; Park, Donghwi
Abstract : Abstract: Ultrasound-guided corticosteroid injection into the carpal tunnel is widely performed for the management of carpal tunnel syndrome. However, this injection may worsen the condition in patients with type 2 diabetes mellitus. Polydeoxyribonucleotide was recently recognized as a substitute for corticosteroid because of its anti-inflammatory effects. A 41-yr-old woman with type 2 diabetes mellitus was admitted to our rehabilitation clinic with a 1-mo history of numbness and tingling in her right hand and first three fingers tips. She declined corticosteroid treatment because of a previous episode of uncontrolled blood glucose levels after corticosteroid injection. Therefore, ultrasound-guided polydeoxyribonucleotide injections into the carpal tunnel were carried out. At the 6-mo follow-up, the patient demonstrated an improvement in the carpal tunnel syndrome symptoms without any complications. Thus, polydeoxyribonucleotide injections into the carpal tunnel can be an alternative to corticosteroid injections for carpal tunnel syndrome if there are limitations because of adverse effects of the latter. Abstract : Supplemental digital content is available in the text.